Estimasi Ragam, Jumlah Kelompok Gen Pengendali Karakter dan Heritabilitas Hasil Tomat di Dataran Rendah - Eka Saputra, Helfi; Wahyuni Ganefianti, Dwi; Salamah, Umi; Sariasih, Yenny; Dwi Ardiansyah, Nico (Jurnal Hortikultura Indonesia, 2019)
Crossing is one technique to expand the genetic diversity. The research objective was to estimate the genetic variability, heritability and number of genes controlling characters tomato yield and yield component in the F2 population crosses TMU-1 xTMU-2 at the low altitude. The research was conducted from April to October 2016 in Kandang Limun, Bengkulu city with a height of 10 m (low altitude). Estimates of genetic variability, heritability and number of genes controlling the yield character is determined based on the mean and variance in the population. The results showed all of the characters that were tested had a number of genes controlling the character as much as one gene. Characters are controlled by a single gene is expected fixation genes to be rapid in some early cycles of selection. Eight characters had a high heritability. Each character and heritability is flowering day (52.90%), the number of fruits per plant (92.99%), fruits length (77.10%), fruits diameter (71.76%), the number of locul fruits (85.68%), thick flesh (73.05%), total soluble solids (89.77%) and fruit weight per plant (65.19%). Keywords: diversity, heritability, low altitude, number of genes group, yield component